2018
DOI: 10.1253/circj.cj-17-1285
|View full text |Cite
|
Sign up to set email alerts
|

Non-Ischemic Heart Failure With Reduced Ejection Fraction Is Associated With Altered Intestinal Microbiota

Abstract: Non-ischemic HFrEF patients exhibited multidimensional differences in intestinal microbial communities compared with healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 36 publications
(37 reference statements)
3
27
0
1
Order By: Relevance
“…The preponderance of genera belonging to Proteobacteria in control subjects and of the genera Streptococcus and Dorea in AF were similar to our results. It is noteworthy that patients with AF shared the enrichment of numerous microbial flora, such as Streptococcus and Dorea, demonstrated in hypertension [36], heart failure [37], and CAD [4]. An excess of these genera agrees with a recent study showing that overgrowth of genera is related to plasma and fecal indole [20].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The preponderance of genera belonging to Proteobacteria in control subjects and of the genera Streptococcus and Dorea in AF were similar to our results. It is noteworthy that patients with AF shared the enrichment of numerous microbial flora, such as Streptococcus and Dorea, demonstrated in hypertension [36], heart failure [37], and CAD [4]. An excess of these genera agrees with a recent study showing that overgrowth of genera is related to plasma and fecal indole [20].…”
Section: Discussionsupporting
confidence: 86%
“…However, there is no evidence to date linking the relationship between hemodynamics and gut microbiota. The relationship between the gut microbiota and heart failure, in which cardiac output may be reduced, has been reported [9,37]. However, the results of those studies were contrasting, and the specific gut microbial phenotype of heart failure remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In the wild, due to food shortage, protein and fat intake decreased, and the Bacteroidetes content increased to help host to increase their nutrition. A disruption of the symbiosis between the microbiota and host is known as dysbiosis and is described in multiple chronic diseases, such as obesity and malnutrition (Castaner et al 2018;Zhang et al 2018;Jeong et al 2019), neurological disorders (Kurokawa et al 2018;Quagliariello et al 2018;Sun and Shen 2018), inflammatory bowel disease (IBD) (Costa et al 2012;Roche-Lima et al 2018), metabolic syndrome (Zhao et al 2018), cancer and other diseases (Katsimichas et al 2018;Lu et al 2018;Panebianco et al 2018;Pulikkan et al 2018;Zitvogel et al 2018). We presume that the health of the wild group of Tibetan wild asses was better than the captive group.…”
Section: Discussionmentioning
confidence: 99%
“…It also negatively impacts upon the immune system [ 20 ], the cardiovascular system [ 21 ], the brain, and behaviour [ 22 ]. There have been a considerable number of reports in recent years demonstrating that the composition of the microbiome can significantly impact not only an individual’s risk of systemic disease [ 22 , 23 , 24 ], but also the extent of disease progression [ 25 , 26 , 27 , 28 ]. It has been demonstrated that modulating the microbial composition may be a promising therapeutic avenue [ 29 ] for cancer [ 30 ], auto-immune [ 31 , 32 ], cardiovascular and kidney diseases [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%